ACCOUNTING IN THE SMALL LIBERAL-ARTS COLLEGE. - Larimore, T. R. (The Accounting Review, 1937)
A striking development has taken place in recent years in the growth and expansion of commercial departments in small liberal-arts colleges. As a result of this development many of these colleges have incorporated business courses. It is the purpose of the paper to examine the nature of this development and to indicate the place of accounting courses in the expansion of business curriculum. Accounting in a liberal-arts curriculum has had considerable discussion in recent years by men interested primarily in the teaching of accounting. It will be of interest to notice the relationship between the stated purposes of business departments in liberal-arts college and aims and purposes of the liberal-arts college itself. It is being recognized in a greater degree that courses in accounting and other business subjects meet the generally accepted purposes of a liberal-arts curriculum and in meeting the general requirements of the liberal-arts college by examining offerings of small liberal-arts colleges and noting the relative emphasis placed upon accounting courses in the curriculum.